Assessing language background and experiences among heritage bilinguals - Macbeth, Alessandra; Atagi, Natsuki; Montag, Jessica L.; Bruni, Michelle R.; Chiarello, Christine (Frontiers in Psychology, 2022)
The language backgrounds and experiences of bilinguals have been primarily characterized using self-report questionnaires and laboratory tasks, although each of these assessments have their strengths and weaknesses. The Electronically Activated Recorder (EAR), an audio recording device, has recently become more prominent as a method of assessing real-world language use. We investigated the relationships among these three assessment tools, to understand the shared variance in how these measures evaluated various aspects of the bilingual experience. Participants were sixty Southern California heritage bilingual college students who spoke a variety of heritage languages and began to learn English between the ages of 0- to 12-years. Participants completed both self-report and laboratory-based measures of language proficiency and use, and they wore the EAR for four days to capture representative samples of their day-to-day heritage language (HL) use. The results indicated that self-reported HL use and English age of acquisition were significant predictors of real-world language use as measured by the EAR. In addition, self-reported HL proficiency and laboratory-based HL proficiency, as measured by verbal fluency, were mutually predictive. While some variability was shared across different assessments, ultimately, none of the measures correlated strongly and each measure captured unique information about the heritage bilingual language experience, highlighting the dissociation between language experience measured at a single point in time and an accumulated life history with a heritage language. These findings may provide guidance for bilingualism researchers about which assessment tool, or combination of tools, may be best for their specific research questions.